Changing preferences through experimental games: Evidence from sanitation and hygiene in Tamil Nadu - Stopnitzky, Yaniv (International Food Policy Research Institute, 2016)
Much policy interest in sanitation and hygiene promotion focuses on changing behavior and increasing demand for these goods. Yet the effectiveness of large-scale interventions has been mixed, in large part because of the difficulty of changing attitudes on deeply rooted behaviors. This study tests whether an experiential learning exercise structured around an experimental game can be used to shift preferences around sanitation and hygiene. A minimum coordination game is adapted to the sanitation and hygiene setting by linking game choices to real-world investment decisions and payoffs in terms of health and status. Individuals from 20 villages in rural Tamil Nadu were randomly assigned to one of three groups: one that played a game in which communication between rounds was allowed, another that played a game in which communication was prohibited, and a control group that only completed a survey. Based on a comparison of survey responses across treatment arms, the game improved stated preferences in relation to sanitation and hygiene. This effect was larger when communication was allowed, and men responded on average more strongly than women across both versions of the game. These results suggest that experimental games can be a valuable tool not only for the study of decision making but for improving participants’ knowledge and pro-sanitation preferences.